Making Sense of Biodiversity: The Affordances of Systems Ecology - Andersson, Erik; McPhearson, Timon (Frontiers in Psychology, 2018)
We see two related, but not well linked, fields that together could help us better understand biodiversity and how it, over time, provides benefits to people. The affordances approach in environmental psychology offers a way to understand our perceptual appraisal of landscapes and biodiversity and, to some extent, intentional choice or behaviour, i.e. a way of relating the individual to the system s/he/it lives in. In the field of ecology, organism specific functional traits are similarly understood as the physiological and behavioural characteristics of an organism that informs the way it interacts with its surroundings. Here, we review the often overlooked role of traits in the provisioning of ecosystem services as a potential bridge between affordance theory and applied systems ecology. We propose that many traits can be understood as the basis for the affordances offered by biodiversity, and that they offer a more fruitful way to discuss human-biodiversity relations than do the taxonomic information most often used. Moreover, as emerging transdisciplinary studies indicate, connecting affordances to functional traits allows us to ask questions about the temporal and two-way nature of affordances and perhaps most important, can serve as a starting point for more fully bridging the fields of ecology and environmental psychology with respect to how we understand human-biodiversity relationships.